Electric Engine Stand with Trolley - Dizon Jr, Rene C.; Abadam, Mark Vincent (Future Science / FSH-PH Publications, 2024)
This study focused on the fabrication of an electric engine stand with trolley. This study aimed to fabricate electric engine stand with trolley and assess its efficiency in terms of safety, dura-bility and functionality. The project followed a systematic approach including planning and designing, gathering all the materials, con-struction, testing, revision and finalization phases. The finish device Electric, Engine Stand with Trolley, demonstrated capabilities such as that the engine stand can lessen the time consumption in assem-bling and disassembling of an engine and it is safe for automotive technician to avoid accidents. The project evaluation revealed High-ly Efficient that the Electric Engine Stand with Trolley fulfilled its purpose of providing safe, durable, and functional equipment that automotive student can use effectively when assemble and disas-semble of engine. In terms of safety, the design incorporates several features aimed at minimizing risks associated with engine handling. The trolley mechanism allows for smooth transportation, reducing the likelihood of accidents during movement. The materials and construction of the Electric Engine Stand with Trolley withstand the rigors of daily use, with a lifespan exceeding industry standards of a Highly Efficient in the level of efficiency. Additionally, its multifunc-tional design accommodates a variety of engine sizes and configura-tions, making it versatile for different automotive tasks. The Electric Engine Stand with Trolley offers notable improvements in efficiency, safety, durability, and functionality, positioning it as an essential tool for modern automotive workshops.